2023
DOI: 10.1007/s10389-022-01802-3
|View full text |Cite
|
Sign up to set email alerts
|

Post-COVID-19 syndrome: nature of symptoms and associated factors

Abstract: Aim Post-COVID-19 syndrome is defined as continuous symptoms related to SARS-CoV-2 infection, which can persist for several weeks or months. Previous studies identified risk factors associated with post-COVID-19 syndrome, including female sex, hypertension, and allergic respiratory diseases. This study aims to investigate the frequency of this syndrome among Arabic patients. Subject and methods A cross-sectional study was conducted from March to August 2022. The study i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 37 publications
0
4
0
Order By: Relevance
“…As a result, we found that some patients with decompensated cirrhosis also experienced the symptoms of “post-COVID-19 syndrome,” such as cough, fatigue, wheezing, and change or even loss of taste. [ 23 , 24 ] As described by these patients, these symptoms persisted after COVID-19 illness, and in this study, were categorized as the “post-COVID-specific symptom cluster.” The findings of our study, along with those of others [ 25 ] have suggested that these syndromes impact patients’ quality of life to varying degrees.…”
Section: Discussionmentioning
confidence: 79%
“…As a result, we found that some patients with decompensated cirrhosis also experienced the symptoms of “post-COVID-19 syndrome,” such as cough, fatigue, wheezing, and change or even loss of taste. [ 23 , 24 ] As described by these patients, these symptoms persisted after COVID-19 illness, and in this study, were categorized as the “post-COVID-specific symptom cluster.” The findings of our study, along with those of others [ 25 ] have suggested that these syndromes impact patients’ quality of life to varying degrees.…”
Section: Discussionmentioning
confidence: 79%
“…Coughing is the most common symptom of COVID-19 sequelae and is present in approximately 23% to 57% of COVID-19 survivors in all countries, and is highly prevalent in both mild and severe cases [ 173 , 174 ]. Cough can persist for months, with a prevalence of up to 2.5% even after one year of recovery [ 175 ], making it a major source of distress for patients.…”
Section: Therapeutic Potential Of Naringin and Naringenin In Long Covidmentioning
confidence: 99%
“…The pathogenesis of post-COVID syndrome involves multiple mechanisms that result in various clinical manifestations. 26 The post-COVID-19 patients were given 10 minutes of inhalation of essential oils containing a mixture of Thymus vulgaris, Citrus sinensis, Eugenia caryophyllus, and Boswellia carterii (essential oils) twice per day for 14 days, which resulted in a significant decrease in fatigue in the Intervention Group. Nevertheless, one participant in the Intervention Group reported experiencing headaches and withdrew on day-13.…”
Section: Efficacymentioning
confidence: 99%